Molecular identification of 26 syntaxin genes and their assignment to the different trafficking pathways in Paramecium - Kissmehl, Roland; Schilde, Christina; Wassmer, Thomas; Danzer, Carsten; Nuehse, Kathrin; Lutter, Kaya; Plattner, Helmut (My University, 2007)
SNARE proteins have been classified as vesicular (v)- and target (t)-SNAREs and play a central role in the various membrane interactions in eukaryotic cells. Based on the Paramecium genome project, we have identified a multigene family of at least 26 members encoding the t-SNARE syntaxin (PtSyx) that can be grouped into 15 subfamilies. Paramecium syntaxins match the classical build-up of syntaxins, being tail-anchored membrane proteins with an N-terminal cytoplasmic domain and a membranebound single C-terminal hydrophobic domain. The membrane anchor is preceded by a conserved SNARE domain of ~60 amino acids that is supposed to participate in SNARE complex assembly. In a phylogenetic analysis, most of the Paramecium syntaxin genes were found to cluster in groups together with those from other organisms in a pathway-specific manner, allowing an assignment to different compartments in a homology-dependent way. However, some of them seem to have no counterparts in metazoans. In another approach, we fused one representative member of each of the syntaxin isoforms to green fluorescent protein and assessed the in vivo localization, which was further supported by immunolocalization of somesyntaxins. This allowed us to assign syntaxins to all important trafficking pathways in Paramecium.
Keywords: exocytosis; Golgi; Paramecium; SNAREs; syntaxin; 540